Early detection of anemia among school children using the World Health Organization Hemoglobin Color Scale 2006 - Desy Rusmawatiningtyas; Dwikisworo Setyowireni; Sri Mulatsih; Sutaryo Sutaryo (Paediatrica Indonesiana, 2009)
Background The high prevalence of anemic children in Indonesiais caused by the high incidence of diseases caused by parasiticinfection such as malaria as well as iron deficiency. Early detectionis needed for early intervention in order to allow optimal growthand development. A simple, economic, and practical tool forearly detection of anaemic children is needed. The WHOrecommended a Hemoglobin Color Scale as a suitable tool forthe detection of anemia.Objective To assess the sensitivity, specificity, and predictivevalues of the WHO Hemoglobin Color Scale for early detectionof anemic children.Methods A cross sectional diagnostic test was conducted inelementary school age children. Samples consisting of two drops ofvenous blood on paper were assessed by two observers (pediatrician& paramedic) using the Hemoglobin Color Scale to visuallydetermine the level of hemoglobin. In addition, the hemoglobinlevel was also measured using a Hematology Analyzer to allow thevisual test results to be compared to the results obtained using thegold standard of analysis. Agreement between these two methodsof analysis was examined using the Cohen's kappa.Results Hemoglobin levels < 11.5 g/dL were detected in 15 of124 (12%) elementary school children. The sensitivity, specificity,positive and negative predictive values when using the HemoglobinColor Scale were 93%, 100%, 100% and 99% respectively for thefirst observer and 100%,99%,93%, and 100% respectively for thesecond observer. The Cohen's Kappa value was 0. 76.Conclusion The WHO Hemoglobin Color Scale 2006 couldbe used as an early detection method for anemia in children.